Societal vulnerability in the context of population aging—Perceptions of healthcare students' in Saudi Arabia - Samarkandi, Osama A.; Aljuaid, Mohammed; Abdulrahman Alkohaiz, Mohammed; Al-Wathinani, Ahmed M.; Alobaid, Abdullah Mohammed; Alghamdi, Abdullah A.; Alhallaf, Mohammed A.; Albaqami, Nawaf A. (Frontiers in Public Health, 2022)
Background and objective: Health care professionals have an important role in increasing awareness and protecting populations from natural disasters and serving as role models. This study aimed to assess the perception of health care students towards societal vulnerability in the context of population aging. Methods: This is a cross-sectional questionnaire-based study conducted among students from two different health colleges over four months from February to May 2021. Descriptive analysis was used to assess the perception, and inferential testing was used to assess the various association of knowledge toward societal vulnerability using SPSS. Results: The majority of respondents were male (69.2%), between 20-24 years of age (91.2%), and studying for a nursing degree (76.6%). Only 4.7% had previously completed a previous degree. The mean score of perceptions on the Ageing and Disaster Vulnerability Scale among nursing students was 42.5 ± 10.3, (0-65) while for paramedicine 48.1± 9.7. (0-65). Similarly, the mean score among male students was 44.1 ±10.5. The mean PADVS total score for the cohort was 43.8 (SD=10.5). The mean PADVS total score for nursing students was significantly lower than paramedic students (42.5 vs 48.1; p<0.001). There was no correlation between PADVS total score and gender, age, area of residence, or previous degree. Participants basing their responses on the wider Saudi Arabian society had a significantly higher PADVS total score than those considering their local community (44.8 vs 42.3; p=0.045). Respondents showed similar levels of concern across all four PADVS subscales. Conclusion: Our results indicate that Saudi health care students perceive older adults are somewhat vulnerable to disasters with significant differences between nursing and paramedic students. Furthermore, we suggest informing emergency services disaster response planning processes about educational intervention to overcome disasters in Saudi Arabia and other countries.